TIMP1 in conditioned media of human adipose stromal cells protects neurons against oxygen-glucose deprivation injury. (1st January 2015) - Du, Shiwei; Mao, Gengsheng; Zhu, Timothy; Luan, Zuo; Du, Yansheng; Gu, Huiying
Highlights: hASC-CM Protected Neuronal Death Induced by OGD. hASC-CM Blocked Activation of Caspase-3. TIMP1 played a role in the neuronal protection of hASC-CM. Abstract: Adipose stromal cells (ASC) can protect neurons when administered to brains due to secreted trophic factors. Our previous studies demonstrated that several neurotrophic factors such as brain-derived neurotropic factor (BDNF) and insulin like growth factor-1 (IGF-1) in ASC conditioned media (ASC-CM) can protect brains against hypoxic-ischemic (HI) injury in neonatal rats. In this study, we demonstrated that human ASC-CM potently blockeds caspase-3 mediated cortical neuronal apoptosis under in vitro oxygen-glucose deprivation (OGD). Interestingly, tissue inhibitor of metalloproteinase 1 (TIMP1), a non neurotrophic factor, played a significant role in the ASC-CM-induced neural protection against OGD. Thus, this study establishes the therapeutic potential of TIMP1 together with other neurotrophic factors in ASC-CM for treating cerebral HI disorders.